HUBUNGAN ANTARA FAKTOR ORGANISASI KERJA DAN BEBAN KERJA TERHADAP STRES KERJA PADA PEKERJA GALANGAN KAPAL DI PT.X - Anis Setyowati; Ida Wahyuni; Ekawati Ekawati (Jurnal Kesehatan Masyarakat (Undip), 2017)
Work of shipbuilding is one of the construction work that is very complex, where there was many kinds of work that must be done parallel. There was a deadline between order and delivery so that when passing through such a deadline will be subject to the penalty is very high so that pressing everyone involved in the industry shipbuilding to work according to the target. The condition that often causes the workers experience work stress. This study aims to analyze the correlation between the work organization factors and workload towards work stress shipbuilding workers in x company. The study is conducted in quantitative design with cross-sectional approach. The instrument used is pulsmeter (to measure their pulse), NASA TLX and Hamilton Anxiety Rating Scale (HARS). The population of shipbuilding workers are 180 workers using the Lemeshow formula and obtained in 124 subjects. Data colleting conducted by inquiries filled by the subjects. Results of statistical tests used Rank Spearmen test, the correlating factors are role in the organization (sig=0,007), career development (sig=0,014), the structure and climate of organization (sig=0,008), and mental workload (sig=0,039). While the non-correlating variables are relationship in the work (sig=0,825) and physical workload (sig=0,284). Thus the companies need to be held a morning exercise before worked so that the mind becomes fresh and can maintain the grounds of the body and can minimize stress.